(untitled) (Palíndromo, 2014)
Serralves Foundation (FS in Portuguese) is a cultural institution of International range that owns a Museum of Contemporary Art with an Educational Service (SE in Portuguese) responsible for organizing programs for the general public, and specially for schools. This paper presents part of an investigation about the Projects with Schools proposed by the SE in 2012/2013, and concerns from the structure and organization of this annual project, to its chief actors and the inter-institutional actions it generates. Its methodology uses material published by the SE and talks held with the main actors of such actions (Educational Service of FS) and with the professionals from schools involved in the project. As a theoretical basis it uses the principles of French, or discursive semiotics.